Analysis of microscopic properties of radiative shock experiments performed at the Orion laser facility. (22nd June 2018) - Rodríguez, R.; Espinosa, G.; Gil, J. M.; Suzuki-Vidal, F.; Clayson, T.; Stehlé, C.; Graham, P.
Abstract : In this work we have conducted a study on the radiative and spectroscopic properties of the radiative precursor and the post-shock region from experiments with radiative shocks in xenon performed at the Orion laser facility. The study is based on post-processing of radiation-hydrodynamics simulations of the experiment. In particular, we have analyzed the thermodynamic regime of the plasma, the charge state distributions, the monochromatic opacities and emissivities, and the specific intensities for plasma conditions of both regions. The study of the intensities is a useful tool to estimate ranges of electron temperatures present in the xenon plasma in these experiments and the analysis performed of the microscopic properties commented above helps to better understand the intensity spectra. Finally, a theoretical analysis of the possibility of the onset of isobaric thermal instabilities in the post-shock has been made, concluding that the instabilities obtained in the radiative-hydrodynamic simulations could be thermal ones due to strong radiative cooling.